Economía colaborativa en Sinaloa: análisis y posturas de empresarios en la industria restaurantera (Journal of Management & Business Studies, 2024)
The current global health and economic crisis caused by COVID-19 has opened the possibility of adopting new business cooperation models to adapt to the challenges presented by the environment, one of them is the so-called collaborative economy which is managing to consolidate an economic concept with a market value of more than 100 million euros, unlike Mexico, these schemes are hardly appreciated in the restaurant industry. Based on the grounded theory and with the objective of analyzing whether entrepreneurs recognize the concept of what the collaborative economy represents from a perspective of support for the benefit of the changes that have occurred in the industry, we have examined 4 representative CEOs of organizations positioned in the gastronomic sector of Sinaloa-Mexico. The methodology used is qualitative with a naturalistic approach and the main findings are that gastronomic companies with a vision in the collaborative economy develop a more inclusive and sustainable business model to benefit society since they combine social development and economic growth.
Keywords: economía colaborativa; industria restaurantera; COVID 19; modelo económico